ENABLING FACTORS FOR CAPACITY BUILDING IN THE INSURANCE SECTOR - Kajwang, Ben (European Journal of Human Resource, 2022)
Purpose: This paper makes a contribution to the existing body of research by investigating the elements that make capacity building in the insurance industry possible, focusing specifically on life and non-life premiums. The industry of insurance has the potential to be an important driver of both financial and economic growth. The industry has the ability to foster new investments, innovation, and competitiveness if it can lessen the impact of huge losses and the associated level of uncertainty. Insurance companies, in their capacity as financial intermediaries with extended time horizons for investment, can make a contribution to the development of long-term financial instruments that can be used to fund business investment and housing. Methodology: This study focuses mostly on conducting a literature review, specifically one that examines previous research on capacity building in the insurance sector and a search of the relevant literature was incorporated into the work technique. Relevant seminal references and journal articles for the study were identified using Google Scholar beginning in 2017 and ending in 2022. Findings: The findings indicate that the premiums for the insurance sector are influenced by factors such as the income per capita, the size and density of the population, demographic structures, income distribution, the size of the public pension system, the ownership of insurance companies by states, the availability of private credit, and religion. These elements, along with a number of others, have an impact on the non-life industry. The results reveal that the capacity expansion of the insurance sector can be enabled by a variety of different factors, despite the fact that some of these drivers are structural in nature. Unique Contribution to Theory, Policy and Practice: The studies also suggest that insurance companies should conduct regular monitoring and evaluation in order to determine how successfully they have implemented their various capacity building strategies.